The Molecular Epidemiology of Crithidia Strains in Isfahan City and Surrounding Areas, Iran - Monir Doudi; Mahbubeh Setorki; Gilda Eslami; Seyed Hossein Hejazi (مجله دانشکده پزشکی اصفهان, 2014)
Background: Genotyping of Crithidia species is of high importance in the selection of an appropriate method to control and prevent cutaneous leishmaniasis (CL), determination of the best therapeutic effect of drugs, and preparation and evaluation of the vaccines.